Do progenitor cells from different tissue have the same phenotype? - Godoy, Roberta F.; Alves, Ana Liz Garcia [UNESP]; Gibson, Amanda J.; Lima, Eduardo M. M.; Goodship, Allen E. (Elsevier B.V., 2014)
The purpose of this work was to validate isolation methods for sheep mesenchymal stem cells (MSC) from different sources and to explore the hypothesis that MSC exhibit markers of the same phenotype independent from tissue source. Cells derived from ovine bone marrow, synovial membrane and adipose tissue were characterized using the following markers: CD44, CD45, CD11b and MHC-I. The isolated MSC were cultivated, went through osteogenic, chondrogenic and adipogenic differentiation, and were characterized by flow cytometry using mouse anti-ovine CD44, CD45 and MHC-I monoclonal antibody (mAb), and mouse anti-bovine CD11b mAb. Ovine MSC from all three sources differentiated under chondorgenic, osteogenic and adipogenic conditions. Also, MSC from the three tissues were found to express CD44 and MHC-I but lack of CD11b and CD45. The results obtained revealed that our isolation methods for the different tissues tested are valid and that MSC from the three sources studied have same immunophenotic characteristics. (C) 2014 Published by Elsevier Ltd. All rights reserved.
Keywords: MSC; Ovine; Flow cytometry; Surface markers